Measures of the riskiness of banking organizations: Subordinated debt yields, risk-based capital, and examination ratings - Douglas D. Evanoff; Larry D. Wall (Federal Reserve Bank of Atlanta, 2001)
Recently there have been a number of recommendations to increase the role of subordinated debt (SND) in satisfying bank capital requirements as a preferred means to discipline the risk-taking behavior of systemically important banks. One such proposal recommended using SND yield spreads as the triggers for mandatory supervisory action under prompt corrective action guidelines introduced in U.S. banking legislation in the early 1990s. Currently such action is prompted by bank capital ratios. Evidence from previous research suggests that yield information may be a better predictor of bank problems. This paper empirically analyzes potential costs and benefits of using SND signals to trigger prompt corrective action.
Keywords: 330; Risk; Debt; Banks and banking; Bank supervision; Bank examination